The Effect of Botulinum Toxin Injection in Cleft Lip Repair - Evan Nuri Bapir; Jalal Hamasalih Fattah (Advanced Medical Journal)
Background & Objectives: Cleft lip and palate are common congenital anomalies that require precise management with main component of repairing lip is the aesthetic outcome. Using botulinum toxin is new method to optimize the resultant scar. The aim of this study is to evaluate the effect of botulinum toxin type A following cleft lip repair on resultant quality of scar.